Complete plastome sequence of Averrhoa carambola L. (Oxalidaceae) - Jo, Sangjin (Mitochondrial DNA B Resour, 2016)
In this study, we determined the complete plastome sequence of Averrhoa carambola L. (Oxalidaceae) (NCBI acc. no. KX364202). To the best of our knowledge, this is the first reported complete plastome sequence from the order Oxalidales. The gene order and structure of the A. carambola plastome are collinear with the typical plastome of land plants. The complete plastome size is 155,965 bp in length and consists of a large single copy region of 87,217 bp and a small single copy region of 17,496 bp, which are separated by a pair of 25,626-bp-long inverted repeat regions. The overall A-T content of the plastome sequence is 61.2%. The plastome contains 111 genes, of which 77 are protein-coding genes, 30 are tRNA genes, and 4 are rRNA genes. Sixteen genes contain one intron and two genes have two introns. A total of 91 simple sequence loci were identified from the genome. Phylogenetic analysis revealed that A. carambola is a sister group of Euonymus japonicus with 100% bootstrap support.